1986
DOI: 10.1007/bf01965002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological studies of antigen-induced arthritis in BALB/c mice I. Characterization of the arthritis and the effects of steroidal and non-steroidal anti-inflammatory agents

Abstract: Chronic monoarticular allergic arthritis was induced in BALB/c mice using methylated BSA as antigen and Freund's complete adjuvant, together with Bordetella pertussis as a secondary adjuvant. The optimum conditions for induction of chronic persistent arthritis and the histological characteristics of the arthritic lesion are described. Both the synovitis and erosive progression of the arthritis could be suppressed by daily treatment with prednisolone (1-10 mg/kg) or dexamethasone (0.5-2.5 mg/kg) for 4 weeks com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…This dosage has been administered before and turned out to be well tolerated in mice. 27,28 Treatment was started on day after subtotal pancreatectomy and lasted for 28 consecutive until sacrifice of the animals. To avoid unnecessary suffering, it was planned to sacrifice all animals in each group, if one animal met Buckwell's criteria indicating severe distress.…”
Section: Methodsmentioning
confidence: 99%
“…This dosage has been administered before and turned out to be well tolerated in mice. 27,28 Treatment was started on day after subtotal pancreatectomy and lasted for 28 consecutive until sacrifice of the animals. To avoid unnecessary suffering, it was planned to sacrifice all animals in each group, if one animal met Buckwell's criteria indicating severe distress.…”
Section: Methodsmentioning
confidence: 99%
“…A monarticular arthritis was induced in C57B116 mice with mBSA as previously described (22,23). Briefly, mice were immunized (on day -21) with 100 pl of 1 mg/ml mBSA (Sigma, St. Louis, MO) emulsified in Freund's complete adjuvant supplemented with 1 mglml heat-killed M tuberculosis, strains C, DT, and PN mixed.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental monoarticular arthritis was induced as described previously [1] using procedures similar to those described by BRACKERTZ et al [2]. Inbred category 4 female BALB/c mice obtained from Bantin and Kingman were sensitised by subcutaneous injection, into the flank, of 100 #l of an emulsion comprised of 50 pl of a 2 mg/ml solution of methylated bovine serum albumin (Met-BSA; Sigma) and 50 #1 of Freund's complete adjuvant (FCA; Difco) to which had been added 50/~g Mycobacterium tuberculosis (Weybridge).…”
Section: Induction Of Arthritismentioning
confidence: 99%
“…In the previous paper [1], we described our initial investigations into the suitability of the antigen-induced monoarticular arthritis model in mice, originally described by BRACKERTZ et al [2], for pharmacological studies of antirheumatic agents. It was found that established experimental arthritis, as judged histologically, could be suppressed by treatment with the corticosteroids prednisolone and dexamethasone, albeit at high doses, but not by treatment with the non-steroidal antiinflammatory agents (NSAIA's) ibuprofen, flurbiprofen and indomethacin.…”
Section: Introductionmentioning
confidence: 99%